Effect of addition of hydrogen and TiO2 in gasoline engine in various exhaust gas recirculation ratio. (23rd April 2019) - Manigandan, S.; Gunasekar, P.; Poorchilamban, S.; Nithya, S.; Devipriya, J.; Vasanthkumar, G.
Abstract: The effects of hydrogen ratios on combustion and emission characteristics of gasoline engine were studied under different exhaust gas recirculation (EGR), ignition timing and ignition pressure. The test performed in a modified gasoline direct ignition engine at different hydrogen ratios of 0%, 5%, 10% and 25%. In addition, the EGR rate set to 0%, 5%, 10% and 20% to study the combustion and emission characteristics. Addition to the different hydrogen fractions, 5% of TiO2 is added to increase the combustion characteristics with reduced emission. Regarding the results of the current study, the engine torque increases by 15% due to the addition of hydrogen in gasoline, while mechanical efficiency is improved by achieving a large throttle opening. At the same time, NOx emission decreased by 62% compared to the unmodified engine due to the influence of EGR, hydrogen ratio and high oxygen concentration TiO2 . Moreover, the emission of CO and HC also reduced due to the influence of hydrogen fuel. Additionally, few more tests are taken to monitor the effect of the injection pressure for the hydrogen fuel. Higher injection reports higher effective thermal efficiency at 4 MPa and lower NOx. Reasonable injection pressure results in shorten flame development period. Highlights: The effects of hydrogen addition with EGR on combustion and emission characteristics were analyzed. Hydrogen direct injection is an effective method to offer dual mode injection in gasoline engine. Hydrogen improves engine performance especially at 20% EGR. The combined effect of TiO2, EGR and hydrogen reduces the emission of CO, HC and NOx.